DETERMINANTS OF FINANCIAL RESOURCES MOBILISATION OF INTEREST-FREE COOPERATIVE SOCIETIES IN ILORIN, KWARA STATE, NIGERIA - Jimoh, Abdulrazaq Taiye (International Journal of Islamic Business & Management, 2021)
Interest-free Cooperative society is introduced as a mirror of conventional cooperatives though on the principle of Islamic finance, to mobilise financial resources with the aim of promoting the socio-economic welfare of their members. There is however some restriction to the quantity of savings that could be mobilized. The study therefore assessed the determinants of savings mobilization in interest-free cooperative in Ilorin Kwara State. Data were collected with the use of questionnaire which was administered on 365 members of institution-based interest-free cooperative societies in Ilorin metropolis. Kaiser-Meyer-Olkin (KMO) and Cronbach’s alpha tests were performed to establish the validity and reliability of the research instrument. Logistic regression analysis was conducted and it was found that mode of saving, credit administration, internal governance and member’s awareness have positive effect on volume of savings mobilized and the effects are significant at 5% and 1% level of significance. The study concluded that the mode of savings, credit administration, internal governance, and members awareness affect resources mobilization of Islamic cooperatives in Ilorin metropolis. Direct deduction of savings from salaries, higher level of transparency and accountability, sensitization campaign are recommended for effective and efficient financial resources mobilization in interest-free cooperative societies.